Atypical bacterial pneumonia in the HIV-infected population (2017)
ABSTRACT: Human immunodeficiency virus (HIV)-infected individuals are more susceptible to respiratory tract infections by other infectious agents (viruses, bacteria, parasites, and fungi) as their disease progresses to acquired immunodeficiency syndrome. Despite effective antiretroviral therapy, bacterial pneumonia (the most frequently occurring HIV-associated pulmonary illness) remains a common cause of morbidity and mortality in the HIV-infected population. Over the last few decades, studies have looked at the role of atypical bacterial pneumonia (i.e. pneumonia that causes an atypical clinical presentation or responds differently to typical therapeutics) in association with HIV infection. Due to the lack of available diagnostic strategies, the lack of consideration, and the declining immunity of the patient, HIV co-infections with atypical bacteria are currently believed to be underreported. Thus, following an extensive database search, this review aimed to highlight the current knowledge and gaps regarding atypical bacterial pneumonia in HIV. The authors discuss the prevalence of Chlamydophila pneumoniae, Mycoplasma pneumoniae, Coxiella burnetii, Legionella species and others in the HIV-infected population as well as their clinical presentation, methods of detection, and treatment. Further studies looking at the role of these microbes in association with HIV are required. Increased knowledge of these atypical bacteria will lead to a more rapid diagnosis of these infections, resulting in an improved quality of life for the HIV-infected population.